Experimental study on dynamic interaction between ground fissure and diagonal three-section subway tunnels - Liu, Lei; Ren, Zhilin; Peng, Weiheng; Yan, Jinkai (Frontiers in Earth Science, 2024)
In this study, the soil acceleration, earth pressure and contact pressure of a three-section subway tunnel under dynamic loading of a subway train in a ground fissure environment were observed and analyzed by physical modeling tests, and the effects of the presence and activity of the ground fissure and tunnel segmentation were discussed. The results show that the vibration generated by the subway traveling will have different degrees of attenuation when propagating in all directions in the soil layer, and the ground fissure has a damping effect on the subway vibration. The attenuation and enhancement of acceleration by ground fissure is affected by the activity and propagation direction of ground fissure. The distribution of additional earth pressure is affected by the ground fissure, soil contact state, which is related to the ground fissure activity state. The ground fissure activity on the contact additional pressure mainly focuses on the bottom and top of the tunnel and there are differences in the location of the hanging wall and footwall. Three-section tunnels have a stronger vibration response and vibration attenuation than monolithic tunnels due to the influence of segmentation. Based on the consideration of the effects of ground fissure and tunnel segmentation, the tunnel design mainly takes into account the amount of ground fissure activity and determines the structural measures, the tunnel structure at the location of the ground fissure is strengthened, in addition to the vibration attenuation measures for the segmented tunnels when crossing the ground fissure. The discussion of mechanical response and design measures in the study helps to reduce the geohazard risk of ground fissures on urban underground transportation infrastructure.